TEM of neutron, proton and self-ion irradiation damage in FeCr alloys - Haley, JC (2018)
In the absence of a high-flux fusion-neutron irradiation source, the microstructural and mechanical changes expected within materials exposed to a nuclear-fusion environment must be replicated by fission-neutron and other surrogate-particle irradiations. This study uses transmission electron microscopy (TEM) to compare the microstructural defects produced in FeCr alloys during exposure to neutrons, protons, and self-ions. Alloys of Fe6Cr and Fe9Cr were irradiated using fission-neutrons, 2.0MeV Fe+ ions and 1.2MeV protons at similar temperatures (~300C) and similar doses (~2.0dpa). The neutron-irradiated alloys contained a population of interstitial dislocation loops with b=<111> (>70%) and b=<100>. The visible dislocation loops were on average ~5nm in size, and the density varied from 2±1 x1014cm-3 in the matrix to 1.2±0.3 x1017cm-3 close to helical dislocation lines. Dislocations loops were mostly clustered around sub-grain boundaries and helical-dislocations. Helical-dislocations formed from initially straight screw dislocations experiencing radial-climb in response to a vacancy-biased defect flux. Small chromium clusters were identified in the neutron-irradiated Fe6Cr, and chromium α’-phase precipitates were identified in the Fe9Cr. Self-ion irradiation produced mostly homogeneously distributed dislocation loops (6-7nm on average), but with a greater fraction of <100> loops (~40%) than was seen in the neutron-irradiated alloys. The self-ion irradiated Fe6Cr and Fe9Cr contained only vacancy-type loops, unlike the neutron or proton irradiated sample which contained only interstitial loops. Chromium remained in solution in both ion-irradiated samples. Proton-irradiated Fe9Cr contained dislocation loops close to helical-dislocation segments, similar to the neutron-irradiated sample. Chromium α’-phases were also identified. The proton-irradiated Fe6Cr contained much larger loops (~13nm on average) than the neutron or ion-irradiated alloys, and chromium was shown to have segregated on and around these loops. Both proton-irradiated alloys contained large voids (>4nm and up to 12nm) at a density greater than 1016cm-3. In the neutron and ion-irradiated alloys, voids were mostly <2nm.